Kriminalisasi Terhadap Perempuan dalam Makna Perzinaan; Studi Komparasi Antara Sistem Hukum Positif dan Pandangan Ulama Mazhab - Ashari, Hardianti; Hasan, Hamzah (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to analyze how the criminalization of women in the meaning of adultery according to positive law and the views of mazhab scholars. In answering the problems above, the authors use Library Research which is guided by the management of data obtained from several literatures. The sources of data obtained include secondary data and primary data. This research approach using a qualitative approach is something that is based on a literature study by exploring scientific works that are directly related to the object being studied and analyzing in the literature that has relevance to the problem discussed, then reviewing and then concluding. The results of this study are how then the implementation of article 284 of the Criminal Code in society is contradictory. The public view is much more complex about adultery and always clashes with religious values so that in determining the law it is always based on religious values. So that in the expansion of the meaning of adultery, it has the potential to criminalize and discriminate against women. Likewise with the views of Imam Shafi'i and Imam and Imam Maliki which in his view still contains elements of gender bias. Where he places women as the source of sin and in making decisions, he always puts his feelings first so that he is not allowed to be a witness in adultery cases, even though there should be no discrimination against women in this regard. Because women also have their own existence, which is equal to men, then as in the case of testimony, they should not only look at it from a biological perspective, but pay more attention to the aspects of integrity, quality, morality and human capacity itself